The act of living. The life in the mirror of the speculative philosophy (Aristotle, Bergson, Gentile) (Nóema, 2012)
The subject of the essay is the nature of living and precisely its activity. In order to try and answer we will make reference to two great philosophers of the 20th century: Henri Bergson and Giovanni Gentile. They both critically tackled the Aristotelian notion of the pure act, a mostly theological and speculative notion. They both re-formulated it just to dispute the physical and metaphysical concept of change elaborated by Aristotle and to elevate the change to Absolute. We are often used to attribute to both of them an aversion towards science. The thesis discussed in this essay is rather the opposite. In thinking the act of living as enérgeia, they contributed to emancipate the science of living from what of metaphysically naïve it contained and still keeps to contain.
Keywords: Giovanni Gentile; Henri Bergson; Gilles Deleuze Speculative philosophy; Change; Pure act Science of living; Praxis/poiesis; Élan vital; Virtuality